Major Depressive Disorder as a Driver of Dual Systems Model Development During Adolescence and Emerging Adulthood Among Justice-Involved Youth: Is Salience Age-Graded? - Wojciechowski, Thomas W. (International journal of offender therapy and comparative criminology, 2025)
The dual systems model is a psychological framework centered on differential development of sensation-seeking and impulse control during adolescence and emerging adulthood with implications for understanding antisocial behavior. However, there is a dearth of research which has examined mental illness as a driver of differential development of these constructs. This study examined major depressive disorder as a risk factor for elevated sensation-seeking and diminished impulse control and tested to determine whether the salience differed by age. The Pathways to Desistance data were analyzed. Mixed effects models examined the direct effect of major depressive disorder on dual systems outcomes and test for moderation by age. Findings indicated that major depressive disorder at baseline was associated with increased sensation-seeking and diminished impulse control. Relationships did not differ in salience based on age. Results suggest that treatment effective for addressing depression may have relevance for mitigating the impact of the disorder on cognition.